Anomalous electronic properties in layered, disordered ZnVSb - Bensen, Erik A.; Ciesielski, Kamil; Gomes, Lídia C. [UNESP]; Ortiz, Brenden R.; Falke, Johannes; Pavlosiuk, Orest; Weber, Daniel; Braden, Tara L.; Steirer, Kenneth X.; Szymański, Damian; Goldberger, Joshua E.; Kuo, Chang-Yang; et al. (American Physical Society (APS), 2021)
New materials discovery is the driving force for progress in solid state physics and chemistry. Here we solve the crystal structure and comprehensively study physical properties of ZnVSb in the polycrystalline form. Synchrotron x-ray diffraction reveals that the compound attains a layered ZrSiS-type structure (P4/nmm, a = 4.09021(2) Å, c = 6.42027(4) Å). The unit cell is composed of a 2D vanadium network separated by Zn-Sb blocks that are slightly distorted from the ideal cubic arrangement. A considerable amount of vacancies were observed on the vanadium and antimony positions; the experimental composition is ZnV0.91Sb0.96. Low-temperature x-ray diffraction shows very subtle discontinuity in the lattice parameters around 175 K. Bonding V-V distance is below the critical separation of 2.97 Å known from the literature, which allows for V-V orbital overlap and subsequent metallic conductivity. From ab initio calculations, we found that ZnVSb is a pseudogap material with an expected dominant vanadium contribution to the density of states at the Fermi level. The energy difference between the antiferromagnetic and nonordered magnetic configurations is rather small (0.34 eV/f.u.). X-ray photoelectron spectroscopy fully corroborates the results of the band structure calculations. Magnetic susceptibility uncovered that, in ZnVSb, itinerant charge carriers coexist with a small, localized magnetic moment of ca. 0.25 μB. The itinerant electrons arise from the ordered part of the vanadium lattice. Fractional localization, in turn, was attributed to V atoms neighboring vacancies, which hinder full V-V orbital overlap. Furthermore, the susceptibility and electrical resistivity showed a large hysteresis between 120 K and 160 K. The effect is not sensitive to magnetic fields up to 9 T. Curie-Weiss fitting revealed that the amount of itinerant charge carriers in ZnVSb drops with decreasing temperature below 160 K, which is accompanied by a concurrent rise in the localized magnetic moment. This observation together with the overall shape of the hysteresis in the resistivity allows for suggesting a plausible origin of the effect as a charge-transfer metal-insulator transition. Ab initio phonon calculations show the formation of a collective phonon mode at 2.8 THz (134 K). The experimental heat capacity reflected this feature by a boson peak with Einstein temperature of 116 K. Analysis of the heat capacity with both an ab initio perspective and Debye-Einstein model revealed a sizable anharmonic contribution to heat capacity, in line with disordered nature of the material. Further investigation of the electron and phonon properties for ZnVSb is likely to provide valuable insight into the relation between structural disorder and the physical properties of transition-metal-bearing compounds.